Strategy of Nannochloropsis Against Environment Starvation: Population Density and Crude Lipid Contents - Hudaidah, Siti; Muhaemin, Moh; ., Rosdinar (Maspari Journal : Marine Science Research, 2013)
Nannochloropsis sp., an unicellular marine microalgae, has potential function as a food source for fish larvae and in chemical industry. Microenvironmental conditions, especially nitrogen and salinity stress in marine ecosystems, became major factor affecting the growth of Nannochloropsis sp.The aim of the experiment was to study effect of different salinities and nitrogen dosages to the growth and lipid contents of Nannochloropsis sp. cells.The experiment was arranged in factorial with three replicates. The first factor was salinity (28 ppt and 38 ppt), and the second factor was nitrogen dosage (100% and 50%). Results of the experiments indicated that nitrogen starvation and high saline concentration affected cell density of Nannochloropsis sp. in different level. The results showed that combination treatments of nitrogen starvation and salinity reduced cell density (treatmant A, B, and D), except in treatment C. Combination of high salinity and high N dosages resulted ini steady growth of Nannochloropsis sp. These results suggest that Nannochloropsis sp. are able to overcome salinity stress (38 ppt) in the presence of optimum concentration of nitrogen in the growth cultures.The results also shows that there were no significant differences of crude lipid content between treatments and no correlation between population density and crude lipid content. These results suggest that no simple correlation between population density and crude lipid concentration. On the other hand, population density was not the only factor affected crude lipid concentration in the microalgae cell.Keyword: Nannochloropsis, population, crude lipid